Pengaruh Model Pembelajaran Game Based Learning Berbantuan Media Spin Wheel terhadap Keaktifan Belajar Peserta Didik - Wilda, Wilda; Syahriani, Syahriani; Maulana, Andi (Department of Biology Education of Universitas Islam Negeri Alauddin Makassar, 2023)
This study aims to determine the effect of the game-based learning model with spin wheel media on the learning activity of grade VIII students at SMP Negeri 2 Marioriwawo. This research included quasi-experimental research with a posttest-only design with non-equivalent groups. The population in this study was 80 students in grade VIII of SMP Negeri 2 Marioriwawo. The sampling technique was purposive sampling, with class VIII 1 as an experimental class with 26 students and class VIII 2 as a control class with 27 students. The research instruments were observation sheets on student learning activities and student learning activity questionnaires. Data analysis was performed with descriptive statistical tests and inferential statistics. According to the findings, the experimental class's average observation sheet score for student learning activities was 83.26, while the control class's average score was 71.33. The results of inferential statistics obtained a signed value of learning activity of 0.000; this proves the value of sign <α = 0.000 < 0.05 so that H0 is rejected and Ha is accepted.These results suggest that the game-based learning model with spin wheel media affects the learning activity of grade VIII students at SMP Negeri 2 Marioriwawo.